Developing an Automated Model-Based Software Testing Tool From the Design Phase - Rasha Gh. Alsarraj; Atica M. Altaie; Esra Zuhair Majeed (IEEE Access)
Software testing involves a number of labor-intensive tasks that, to save resources, should be automated. Model-based software testing is one of the most widely used methods of software quality assurance in the business world is model-based software testing. A potential starting point for creating test paths for testing the target software system is the UML model, which can intuitively explain the dynamic behaviors of a software system under testing. Unfortunately, the lack of strong tool support and automated generating methodologies has resulted in the dearth of practical model-based testing methods for industry practitioners. To address this issue, we suggest automated generation paths using a support tool. The present study proposes a tool for automatically generating test paths from IDEF and UML models to facilitate automated and model-based software testing. This is because early-stage software development process model-based testing was shown to be more efficient; the IDEF model, along with the rule flow model, was utilized in this study, which has never been used to create software test paths. The models were transformed into an XMI file for input, and nodes parser was utilized to construct the test scenarios and assess the active performance of the system. Next came the drawing of a control graph and, finally, the creation of test paths. The test paths generated were measured using a variety of coverage criteria, including edges, actions, branches, and paths. Using the electricity billing system as a case study, the proposed tool achieved high accuracy within authorized coverage limits.